Mengkaji Efek Flypaper di Indonesia: Bukti Setelah Pengalihan Pajak Bumi dan Bangunan Perkotaan-Perdesaan ke Pemerintah Daerah - Afrizal, Raden Muhammad; Khoirunurrofik, Khoirunurrofik (Research and Development Agency Ministry of Home Affairs, 2022)
In order to increase the tax power of local governments, the central government implemented a major reform in 2010 by transferring the Urban-Country Land and Buildings Tax (PBB-P2) to local governments. Although the tax contributes a significant portion of local government revenues, the spending behavior of local governments is questionable, and it is unclear whether public spending has been increased. This study examines the effect of strengthening PBB-P2 policy on increasing local revenue (PAD) and its impact on regional spending patterns, specifically whether there are still flypapers after policy reform. Applying a fixed-effects panel data method to Indonesian local governments from 2005 to 2020, we found that strengthening PBB-P2 policy had a significant positive impact on PAD. The positive effect was found to be significant one year (year +1) after policy implementation in each region, including for the province, district, and city, with the issuance of regional ordinances related to PBB-P2. Interestingly, the significant increase in PAD impacted regional spending patterns. Thus, the flypaper effect phenomenon did not exist from 2005 to 2020. This implies that the central government can selectively empower local governments to levy appropriate local taxes and user fees. This can be done by providing new local tax sources, restructuring tax types, simplifying usage fee types, and harmonizing regional government regulations with the central government.